Palisaded neutrophilic granulomatous dermatitis in a patient with HLA-B27-negative axial spondyloarthritis - Šuler Baglama, Špela (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2022)
Palisaded neutrophilic granulomatous dermatitis (PNGD) is a rare histopathological pattern belonging to a group of cutaneous granulomatous eruptions that typically manifests with asymptomatic skin-colored, erythematous, or violaceous papules or nodules. PNGD can be triggered by various systemic conditions, including medications and autoimmune and autoinflammatory disorders, as well as malignancies; for example, lymphoproliferative disorders. Therefore, in patients with PNGD an extended diagnostic workup is mandatory as well as follow-up in the case of idiopathic PNGD. To the best of our knowledge, this is the first reported case in the literature of PNGD causally related to a relapse of HLA-B27–negative axial spondyloarthritis.
Keywords: dermatitis; granulomatous dermatitis; granulomatozni dermatitis; neutrophilic dermatoses; nevtrofilne dermatoze; palisaded neutrophilic granulomatous dermatitis